2020
DOI: 10.1039/d0ra04986g
|View full text |Cite
|
Sign up to set email alerts
|

ZnO quantum dot-modified rGO with enhanced electrochemical performance for lithium–sulfur batteries

Abstract: ZnO quantum dot-modified rGO was first introduced into lithium–sulfur cathodes, realizing better reaction kinetics and enhanced electrochemical performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 64 publications
0
11
0
Order By: Relevance
“…Figure a shows the synthesis procedure of the WMCNFs hybrids. Through multipoint coordination and hydrogen bonding, BT that contains abundant PhOH groups can be successfully immobilized onto CFs to form BT@CFs . The proactively introduced adjacent PhOH groups in BT can chelate metal ions to obtain the MoO 4 2– /WO 4 2– -grafted precursor (WMBT@CFs) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure a shows the synthesis procedure of the WMCNFs hybrids. Through multipoint coordination and hydrogen bonding, BT that contains abundant PhOH groups can be successfully immobilized onto CFs to form BT@CFs . The proactively introduced adjacent PhOH groups in BT can chelate metal ions to obtain the MoO 4 2– /WO 4 2– -grafted precursor (WMBT@CFs) .…”
Section: Resultsmentioning
confidence: 99%
“…Through multipoint coordination and hydrogen bonding, BT that contains abundant PhOH groups can be successfully immobilized onto CFs to form BT@CFs. 38 The proactively introduced adjacent PhOH groups in BT can chelate metal ions to obtain the MoO 4 2− /WO 4 2− -grafted precursor (WMBT@CFs). 39 Afterward, the precursor is calcined under an inert atmosphere, during which the metal anions convert to WN and Mo 2 C that are in situ embedded in the carbon nanofiber matrix.…”
Section: Resultsmentioning
confidence: 99%
“…Various carbon materials have been employed as sulfur hosts, such as graphene, , hollow carbon spheres, , carbon nanotubes, carbon fibers, , and carbon aerogels. Nevertheless, the weak interaction between the nonpolar carbon materials and the polar polysulfides cannot successfully inhibit the shuttling effect of lithium polysulfides (LiPS) . Polar materials, such as ZnO, , TiO 2 , , MoS 2 , , TiS 2 and Ti 3 C 2 , ,, may successfully capture and promote electrochemical conversion kinetics of LiPS, which is a promising strategy for improving the cycling stability/rate performance of Li–S batteries.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that the QD-based materials feature quantum Hall effects and enriched uncoordinated atomic structures at edge sites. Benefiting from these characteristics, the metal oxide QDs, , carbon QDs, and phosphorus QDs have been widely studied and applied in LSBs, which can promote the chemical immobilization and conversion kinetics of LiPSs. However, the LDH-based QDs have not been employed in LSBs.…”
Section: Introductionmentioning
confidence: 99%
“…36 It has been demonstrated that the QD-based materials feature quantum Hall effects and enriched uncoordinated atomic structures at edge sites. Benefiting from these characteristics, the metal oxide QDs, 37,38 carbon QDs, 39 and phosphorus QDs 40 CoAl-LDH (Cl − ). The CoAl-LDH (Cl − ) was prepared using a salt− acid exchange method.…”
Section: ■ Introductionmentioning
confidence: 99%